A Biocompatible "Split Luciferin" Reaction and Its Application for Non‐Invasive Bioluminescent Imaging of Protease Activity in Living Animals. Issue 3 (9th September 2014) - Godinat, Aurélien; Budin, Ghyslain; Morales, Alma R.; Park, Hyo Min; Sanman, Laura E.; Bogyo, Matthew; Yu, Allen; Stahl, Andreas; Dubikovskaya, Elena A.
Abstract: The great complexity of many human pathologies, such as cancer, diabetes, and neurodegenerative diseases, requires new tools for studies of biological processes on the whole organism level. The discovery of novel biocompatible reactions has tremendously advanced our understanding of basic biology; however, no efficient tools exist for real‐time non‐invasive imaging of many human proteases that play very important roles in multiple human disorders. We recently reported that the "split luciferin" biocompatible reaction represents a valuable tool for evaluation of protease activity directly in living animals using bioluminescence imaging (BLI). Since BLI is the most sensitive in vivo imaging modality known to date, this method can be widely applied for the evaluation of the activity of multiple proteases, as well as identification of their new peptide‐specific substrates. In this unit, we describe several applications of this "split luciferin" reaction for quantification of protease activities in test tube assays and living animals. Curr. Protoc. Chem. Biol . 6:169‐189 © 2014 by John Wiley & Sons, Inc.